2010
DOI: 10.1002/jnr.22457
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression changes associated with long‐lasting synaptic enhancement in hippocampal slice cultures after repetitive exposures to glutamate

Abstract: We have previously shown that repetitive exposures to glutamate (100 muM, 3 min, three times at 24-hr intervals) induced a long-lasting synaptic enhancement accompanied by synaptogenesis in rat hippocampal slice cultures, a phenomenon termed RISE (for repetitive LTP-induced synaptic enhancement). To investigate the molecular mechanisms underlying RISE, we first analyzed the time course of gene expression changes between 4 hr and 12 days after repetitive stimulation using an original oligonucleotide microarray:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
(60 reference statements)
0
20
0
Order By: Relevance
“…Previous studies [50] [163] [164] have already suggested that, following episodes of synaptic activity or during synaptic plasticity processes, the induced immediate-early-genes (IEGs) are characterized by different up-regulation dynamics: nonetheless, the time-course data collected so far in the literature is mainly obtained by microarray analysis, such as [7] [165], and not by a reliable and accurate RT-PCR analysis: more precisely, the information currently available is limited to time-courses with low temporal resolution, i.e. a few time points, and/or concerning a reduced number of genes, such as [15] [18] [19].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [50] [163] [164] have already suggested that, following episodes of synaptic activity or during synaptic plasticity processes, the induced immediate-early-genes (IEGs) are characterized by different up-regulation dynamics: nonetheless, the time-course data collected so far in the literature is mainly obtained by microarray analysis, such as [7] [165], and not by a reliable and accurate RT-PCR analysis: more precisely, the information currently available is limited to time-courses with low temporal resolution, i.e. a few time points, and/or concerning a reduced number of genes, such as [15] [18] [19].…”
Section: Resultsmentioning
confidence: 99%
“…Carp (Ania-4) has been reported to be involved in apoptosis and tubulin polymerization in vitro (Schenk et al, 2007) and in seizures and long-term potentiation in vivo (Schenk et al, 2011;Vreugdenhil et al, 1999;Wibrand et al, 2006). Thus, the DCLK1 proteins might direct the latent process of neural cell differentiation by controlling tubulin formation or by modulating cell viability and subsequent synaptic plasticity (Kawaai et al, 2010;Shu et al, 2006;Vreugdenhil et al, 2007). Expression of Serpinb1a has also been reported to be induced in response to NGF-and PACAP-induced cell differentiation in PC12 cells (Ravni et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hypothalamic magnocellular neurons express VEGF , and VEGF expression in these neurons is increased in response to hyperosmolarity or dehydration [4]. Similar to VEGA, YWHAZ expression affects neural function [36], and YWHAZ message and protein increase in hypothalamic neurons in response to hyperosmolarity resulting from dehydration [20]. The neurotransmitter mediators of this change in expression were not identified.…”
Section: Discussionmentioning
confidence: 99%